2011
DOI: 10.1155/2011/909174
|View full text |Cite
|
Sign up to set email alerts
|

Light-Driven Droplet Manipulation Technologies for Lab-on-a-Chip Applications

Abstract: Droplet-based (digital) microfluidics has been demonstrated in many lab-on-a-chip applications due to its free crosscontamination and no dispersion nature. Droplet manipulation mechanisms are versatile, and each has unique advantages and limitations. Recently, the idea of manipulating droplets with light beams either through optical forces or light-induced physical mechanisms has attracted some interests, since light can achieve 3D addressing, carry high energy density for high speed actuation, and be patterne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
29
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 92 publications
(96 reference statements)
1
29
0
Order By: Relevance
“…In this paper, we present an open surface OEWOD device that significantly improves upon the performance of previously reported open surface devices [4]. We increase the effective capacitance of the dielectric region by adding a dedicated dielectric layer (Al 2 O 3 , 25 nm) of high dielectric constant (ε r of 9.1) and reducing the thickness of the hydrophobic layer, compared to recently reported open surface devices [7].…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…In this paper, we present an open surface OEWOD device that significantly improves upon the performance of previously reported open surface devices [4]. We increase the effective capacitance of the dielectric region by adding a dedicated dielectric layer (Al 2 O 3 , 25 nm) of high dielectric constant (ε r of 9.1) and reducing the thickness of the hydrophobic layer, compared to recently reported open surface devices [7].…”
Section: Introductionmentioning
confidence: 87%
“…We increase the effective capacitance of the dielectric region by adding a dedicated dielectric layer (Al 2 O 3 , 25 nm) of high dielectric constant (ε r of 9.1) and reducing the thickness of the hydrophobic layer, compared to recently reported open surface devices [7]. By increasing the effective capacitance, the threshold voltage was reduced from a few kilovolts [7], [4] to 40.9 V. Low voltage multi-axis droplet manipulation was successfully demonstrated by a multiple-axis contact pad layout surrounding the droplet manipulation region. The device is capable of performing multi-axis droplet motion at speeds as high as 12 mm/sec with a data projector as an optical source.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Since creating discrete droplets and pumping of liquids are done by surface tension alone, EWOD digital microfluidics does not require intricate systems such as channels, pumps and valves to drive and regulate flows [4,5]. In addition, direct manipulation of discrete droplets enables fabrication and operation of highly automated microfluidics systems with more flexibility and higher efficiency [6][7][8][9][10][11][12]. Due to these unique advantages, EWOD digital microfluidics has been used for tremendous applications such as medical [13][14][15][16][17][18][19], display [20,21], optics [22,23], and cooling [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Ding et al demonstrated precise dispensing of volatile droplets in an electrowetting-on-dielectrics (EWOD) platform by introducing the fluid from inside of the needle tip [25]. More recently, Chiou et al and Park et al both integrated light activation technology in EWOD to generate droplets from a channel [26,27]. These systems, however, either require complex experimental setups or an on-chip fluid reservoir to store the fluid to form channels and droplets.…”
Section: Introductionmentioning
confidence: 99%